2020
DOI: 10.3390/su12187398
|View full text |Cite
|
Sign up to set email alerts
|

Cataloguing of the Defects Existing in Aluminium Window Frames and Their Recurrence According to Pluvio-Climatic Zones

Abstract: The sustainability of building envelopes is affected by its windows, since these establish the connection/separation between the indoor rooms and the external environment. They can also lead to problems if they do not offer sufficient protection against external agents. The data source in this research is unprecedented, as it is based on records of court sentences. There is a significant number of cases (1615), which provides high representativeness for the functional reality of windows. The methodology that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The authors of the published papers used various analysis techniques to obtain the suggested solutions for each topic. Listed by key techniques, various techniques such as Analytic Hierarchy Process (AHP) [3,12], the Taguchi method [4], machine learning including Artificial Neural Networks (ANNs) [5,28], Life Cycle Assessment (LCA) [6,7], regression analysis [13,17,19,25,28], Strength-Weakness-Opportunity-Threat (SWOT) [11], system dynamics [16,26], simulation and modeling [10,19,[22][23][24]29,31,32], Building Information Model (BIM) with schedule [21,24,27], and graph and data analysis after experiments and observations [8,9,14,15,18,20,27,[29][30][31][32] are identified.…”
mentioning
confidence: 99%
“…The authors of the published papers used various analysis techniques to obtain the suggested solutions for each topic. Listed by key techniques, various techniques such as Analytic Hierarchy Process (AHP) [3,12], the Taguchi method [4], machine learning including Artificial Neural Networks (ANNs) [5,28], Life Cycle Assessment (LCA) [6,7], regression analysis [13,17,19,25,28], Strength-Weakness-Opportunity-Threat (SWOT) [11], system dynamics [16,26], simulation and modeling [10,19,[22][23][24]29,31,32], Building Information Model (BIM) with schedule [21,24,27], and graph and data analysis after experiments and observations [8,9,14,15,18,20,27,[29][30][31][32] are identified.…”
mentioning
confidence: 99%